“Throw[ing] the Longest Shadows”: The Significance of the Bogus Quotation for Arcadia by Jim Crace - Wojciechowska, Sylwia (Text Matters: A Journal of Literature, Theory and Culture, 2012)
Preceding his Arcadia with a non-existing quotation, Jim Crace proves to be no Arcadian innocent: challenging the shrewdness of his readers, the contemporary novelist seems to take pleasure in inviting them to an intellectual game which begins before the novel unfolds. The highly evocative title and the bogus quotation are bound to evoke associations which become the subject of minute examination in the novel. Its result turns out to be as astounding as the uncommon aphoristic trap laid for the readers. This article examines the significance of the bogus quotation as a part of the novel’s message and a key to its interpretation.